2021
DOI: 10.1007/s43440-020-00195-y
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as a potential drug for treatment of COVID-19: an in-sync review with clinical and computational attributes

Abstract: Introduction COVID-19 cases are on surge; however, there is no efficient treatment or vaccine that can be used for its management. Numerous clinical trials are being reviewed for use of different drugs, biologics, and vaccines in COVID-19. A much empirical approach will be to repurpose existing drugs for which pharmacokinetic and safety data are available, because this will facilitate the process of drug development. The article discusses the evidence available for the use of Ivermectin, an anti-parasitic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 36 publications
(40 reference statements)
2
67
0
4
Order By: Relevance
“… Kaur et al, 2021 ; Li et al, ; Sarma et al, ; Wang et al, .…”
Section: Uncited Referencesunclassified
“… Kaur et al, 2021 ; Li et al, ; Sarma et al, ; Wang et al, .…”
Section: Uncited Referencesunclassified
“…The respondents also utilized antiparasitic drugs, mainly ivermectin. Clinical trials conducted in different countries including Bangladesh showed that ivermectin without and with the combination of other drugs can improve symptoms and reduce mortality, though more evidence is needed on its e cacy [40,41]. One study found that a signi cant number of Bangladeshi populations used ivermectin to relieve COVID-19 symptoms and prophylaxis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Its low toxicity and safety are attributed to the fact that its human target receptors are 'secluded' in the CNS, and IVM has not been shown to cross the blood-brain barrier. In addition, IVM displays a 100-fold greater affinity for parasitic Clchannels compared to the human homologs (35). Moreover, severe detrimental effects in humans were shown only in those who over-dosed using approximately 15.4 mg/kg body weight IVM, which is 77 times above the prescribed dose.…”
Section: Ivermectin the Discovery Of Ivermectinmentioning
confidence: 99%
“…There are currently around 50 clinical trials taking place registered on clinicaltrials.gov, which study the effect of IVM as a prophylactic or therapeutic drug (35). Five studies have completed testing at Phase 1, 2 or 3 and three have posted their real-time results, which are included in Table 1.…”
Section: Clinical Trials the Effect Of Ivermectin On Sars-cov-2 Patientsmentioning
confidence: 99%